2015
DOI: 10.1016/j.quascirev.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on southern hemisphere tropical climate change during the Little Ice Age and Younger Dryas based on glacier modeling of the Quelccaya Ice Cap, Peru

Abstract: a b s t r a c tImproving the late Quaternary paleoclimate record through climate interpretations of low-latitude glacier length changes advances our understanding of past climate change events and the mechanisms for past, present, and future climate change. Paleotemperature reconstructions at low-latitude glaciers are uniquely fruitful because they can provide both site-specific information and enhanced understanding of regional-scale variations due to the structure of the tropical atmosphere. We produce Littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 65 publications
(134 reference statements)
0
13
0
1
Order By: Relevance
“…One method is to drive a glacier model with a range of climate conditions to determine the ones that are compatible with the glacier length records (Allison and Kruss, 1977;Oerlemans, 1986;Jomelli et al, 2011;Luthi, 2014;Malone et al, 2015;Sagredo et al, 2017;Zechetto et al, 2017;Doughty et al, 2017). The temperature and precipitation reconstructions deduced from glacier length fluctuations can also be compared to estimates obtained from other records and climate model results to test the compatibility between the different sources of information.…”
Section: Introductionmentioning
confidence: 99%
“…One method is to drive a glacier model with a range of climate conditions to determine the ones that are compatible with the glacier length records (Allison and Kruss, 1977;Oerlemans, 1986;Jomelli et al, 2011;Luthi, 2014;Malone et al, 2015;Sagredo et al, 2017;Zechetto et al, 2017;Doughty et al, 2017). The temperature and precipitation reconstructions deduced from glacier length fluctuations can also be compared to estimates obtained from other records and climate model results to test the compatibility between the different sources of information.…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation events can also affect ablation through the ways in which cloud cover influences surface energy budgets, in particular, longwave radiation (Hock, 2005), which could introduce additional nonlinear mass-balance responses to climate variability. Previous studies using higher complexity mass-balance models, however, suggest that changing the magnitude of short-term precipitation variability does not affect the average glacier length (Farinotti, 2013; Malone and others, 2015). Many non-linearities are inherent in glacier mass balance, although not all non-linearities produce asymmetries that can affect the mean state.…”
Section: Discussionmentioning
confidence: 95%
“…Changes in average glacier length, however, are usually associated with changes in the mean climate, but a portion of average length changes could also be due to changes in interannual climate variability. Farinotti (2013) and Malone and others (2015), using different numerical modeling techniques, find that the mean length of a glacier retreats upslope as the magnitude of interannual climate variability increases. Thus, the role of interannual climate variability on the average length and mass balance of glaciers warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Palaeo-glacier records, particularly those from tropical latitudes,afford a unique opportunity to help address thesekey problems.Mountain glaciers are sensitive to small changes in temperature (Lowell, 2000;Favier et al, 2004;Oerlemans, 2005;Schaefer et al, 2006;Anderson and Mackintosh, 2012;Rupper and Roe, 2008;Rupper et al, 2012;Malone et al, 2015), as confirmed by their almost global response to modern warming (e.g., Dyurgerov and Meier, 2000), and leave a record of past fluctuations on the landscape in the form of moraines. Recent development of high-resolution glacier chronologies, fuelled by the refinement of cosmogenic surface-exposure dating, hasimproved our understanding of past climate behaviour and provided much-needed insight into the structure of key events including the last glacial maximum (LGM) and subsequent deglaciation.This time period, encompassing the last glacial-interglacial transition,is especiallypertinentasnot only doesit represent the highest-magnitude climate change of the last ~100 Ka, but many of the climatic transitions also were abrupt in nature (Denton et al, 2010).Studying the extant nature of glacier records from the LGM and termination enables comparison of past climate conditions and potential forcing mechanisms, such as greenhouse gases, Milankovitch cycles, and oceanatmosphere reorganisations.…”
mentioning
confidence: 94%